MAGNETIC AND HYPERFINE CHARACTERIZATION OF THE THERMAL TRANSFORMATION CuO - Fe2O3 TO Fe3O4 - Juan D. Betancur; Johans Restrepo; Jhon J. Fernandez; Oswaldo Perez (Momento, 2018)
A magnetic study about the thermal transformation of hematite doped with CuO (Fe2O3 + CuO) is presented. The heat treatment was carried out at a temperature of 375 ± 1 ºC, in a controlled atmosphere composed by 20% hydrogen and 80% nitrogen. Samples were characterized by Mössbauer spectroscopy at room temperature, magnetization as a function of temperature and hysteresis loops at 10K. Our results suggest that both the hyperfine fields and linewidths of the A and B sites remain essentially constant with increasing the CuO concentration, while at the same time a paramagnetic component arises, which is indicative of the appearance of a precipitate or a new phase of Fe-Cu, i.e. there is not an effective incorporation of the copper into the structure of the magnetite. The saturation magnetization falls from approximately 87 emu/g to 78 emu/g, consistent with such a paramagnetic phase. Also, an increase in the coercivity from ~576 Oe up to ~621 Oe by increasing the percentage of CuO from 2% up to 20% is observed. Such increase is also attributed to the paramagnetic phase acting as pinning center for domain walls, besides also de pinning effect due to vacancies induced by the thermal treatment. Finally, an inversion of the magnetization in the Verwey temperature is observed. The data suggest that by means of the synthesis method employed, it is possible to obtain Fe3O4 magnetite particles coexisting with precipitates of Fe-Cu, giving rise to a modification in the magnetic properties and generatingan interesting effect in the magnetization at the Verwey temperature.